Fintech Advancing Sustainable Tourism in Morocco-Spain (International Journal of Applied Research in Management and Economics, 2025)
This research explores the role of Fintech in enhancing tourism management and sustainability of Morocco and Spain, particularly in their co-hosting of the 2030 world cup, while examining how fintech innovations are transforming financial interactions between tourism businesses and travelers, with the potential to improve tourism sustainability, strengthen financial inclusion. The main purpose of this study is to investigate how the integration of fintech can promote sustainable and inclusive tourism by modernizing financial systems, improving service quality, and increasing access to digital financial tools in both developed and emerging market contexts. Specifically, the research aims to: first to identify the drivers and barriers of fintech adopting among tourism stakeholders, secondly to compare the digital readiness and infrastructure of Spain and Morocco, and thirdly to evaluate the extent to which fintech contributes to economic inclusion, transaction security and improved tourist experiences in preparation for the 2030 world cup. The methodology research employed for this study is a mixed approach, while the quantitative includes the collection and analysis of secondary data on Fintech adoption trends, on tourism operations. The qualitative component consists of semi-structured interviews with stakeholders including tourism and fintech experts, to gather insights into the practical challenges and benefits of Fintech in the tourism sector. The study shows that both countries benefit from fintech in touristic firms. Spain demonstrates great ease of use in digital payments but faces cybersecurity challenges. Morocco shows moderate progress but still struggles with infrastructure limitations and uneven digital access.